Unlocking the Lithium Storage Capacity of Aluminum by Molecular Immobilization and Purification. Issue 24 (26th April 2019) - Xia, Guanglin; Zhang, Hongyu; Liang, Ming; Zhang, Jian; Sun, Weiwei; Fang, Fang; Sun, Dalin; Yu, Xuebin
Abstract: Aluminum is regarded as a promising alternative for graphite anode in next‐generation lithium‐ion batteries, but its application is hindered by the simultaneous presence of aluminum oxide and the huge volume changes. Herein, hydrogenation‐induced self‐assembly of robust Al nanocrystals with high purity that are uniformly anchored on graphene is demonstrated. The strong molecular interaction between Al and graphene can not only thermodynamically facilitate the homogenous distribution of Al on graphene but also effectively alleviate the volume changes and preserve the structural integrity of the electrode. More importantly, density functional theory calculations reveal that the absence of oxidation can lower the energy barrier for Li diffusion inside the Al matrix to less than 1/6 of that in an Al matrix with only one monolayer coverage of oxygen. These unique structural features enable the aluminum/graphene nanosheets (Al@GNs) electrode to realize a high reversible capacity of 1219 mAh g −1 and an excellent cycling stability with capacity of 766 mAh g −1 after 1000 cycles at the 3 A g −1 rate. Furthermore, a full cell, comprising an Al@GNs anode and LiFePO4 cathode, exhibits remarkable capacity retention of 96.4% after 100 cycles at the 0.5 A g −1 rate. Abstract : Robust Al nanocrystals with high purity that are uniformly anchored on graphene are synthesized through a hydrogenation‐induced self‐assembly technique. The strong molecular interaction between Al and graphene can not only thermodynamically facilitate the homogenous distribution of Al on graphene but also effectively preserve the structural integrity of the electrode.